Dispositional and situational factors predicting psychological adjustment among fresh students (JAMBITES) in universities (2013)
Psychological adjustment of new students to universities has become an increasing concern to stakeholders (parents, management, teachers, and the students). A major reason is that those who are unable to adjust effectively can get involved in prostitution and cultism- two major problems that are major concern to university administrators in Nigeria. This necessitated the investigation of the influence of dispositional and situational factors on psychological adjustment of jambites' (freshmen). The study involved a sample size of 250 selected from fresh students in the University of Ibadan. The two hypotheses tested with multiple regression statistics were confirmed. Both personality and family background are significant predictors of psychological adjustment among jambites (R2=0.94; p<.05, R2=0.16; p<.05 respectively). It was concluded that all the personality traits contained in the Big five (McCrae & Costa, 1997) are significant predictors of psychological adjustment. Similarly, family background issues are major influences in students' psychological adjustment when they get into the university. The need to do family background and personality profile for newly admitted students was suggested in order to identify those who require assistance for effective adjustment in the university